Periodicity in Attachment Organelle Revealed by Electron Cryotomography Suggests Conformational Changes in Gliding Mechanism of Mycoplasma pneumoniae - Akihiro Kawamoto; Lisa Matsuo; Takayuki Kato; Hiroki Yamamoto; Keiichi Namba; Makoto Miyata (mBio, 2016)
ABSTRACT Mycoplasma pneumoniae, a pathogenic bacterium, glides on host surfaces using a unique mechanism. It forms an attachment organelle at a cell pole as a protrusion comprised of knoblike surface structures and an internal core. Here, we analyzed the three-dimensional structure of the organelle in detail by electron cryotomography. On the surface, knoblike particles formed a two-dimensional array, albeit with limited regularity. Analyses using a nonbinding mutant and an antibody showed that the knoblike particles correspond to a naplike structure that has been observed by negative-staining electron microscopy and is likely to be formed as a complex of P1 adhesin, the key protein for binding and gliding. The paired thin and thick plates feature a rigid hexagonal lattice and striations with highly variable repeat distances, respectively. The combination of variable and invariant structures in the internal core and the P1 adhesin array on the surface suggest a model in which axial extension and compression of the thick plate along a rigid thin plate is coupled with attachment to and detachment from the substrate during gliding. IMPORTANCE Human mycoplasma pneumonia, epidemic all over the world in recent years, is caused by a pathogenic bacterium, Mycoplasma pneumoniae. This tiny bacterium, about 2 µm in cell body length, glides on the surface of the human trachea to infect the host by binding to sialylated oligosaccharides, which are also the binding targets of influenza viruses. The mechanism of mycoplasmal gliding motility is not related to any other well-studied motility systems, such as bacterial flagella and cytoplasmic motor proteins. Here, we visualized the attachment organelle, a cellular architecture for gliding, three dimensionally by using electron cryotomography and other conventional methods. A possible gliding mechanism has been suggested based on the architectural images.